Discussing the Effects of Poor Health Literacy on Patients Facing HIV: A Narrative Literature Review - Rocco Palumbo (Kerman University of Medical Sciences, 2015)
Background Scholars describe poor health literacy as a "silent epidemic," which is challenging the functioning of healthcare systems all over the world. Health literacy is mainly meant as an individual trait which concerns the ability to obtain, process, and understand basic health information in order to effectively navigate the health system. Low health literate patients perceive poor self-efficacy dealing with their health conditions, are not willing to be involved in the provision of care, show larger risks of hospitalization and mortality, and are not aware about the determinants of well-being. Hence, limited health literacy has been associated with inadequate management of long-term conditions; nonetheless, several authors argue that health literacy has been an overlooked factor dealing with HIV. Methods This study is aimed at discussing the effects of poor health literacy on people living with HIV, drawing from the findings of a narrative literature review which involved 41 papers retrieved from the databases "Scopus-Elsevier" and "PubMed." Results The scientific literature is not consistent dealing with the relationship between health literacy and HIV treatment. For example, health literate patients seem to better understand their health conditions; on the other hand, people living with poor health literacy are likely to report higher compliance with providers' prescriptions, blindly trusting healthcare professionals. Conclusions Poor health literacy is a social barrier to access healthcare services and to appropriate health treatment among patients living with HIV. Tailored interventions should be aimed at enhancing the health skills of patients affected by HIV infection to improve their ability to navigate the health system.